Stent Retriever Thrombectomy for Anterior vs. Posterior Circulation Ischemic Stroke: Analysis of the STRATIS Registry - Jahan, Reza; Liebeskind, David S.; Zaidat, Osama O.; Mueller-Kronast, Nils H.; Froehler, Michael T.; Saver, Jeffrey L. (Frontiers in Neurology, 2021)
Background and Purpose: The benefits of mechanical thrombectomy (MT) in vertebrobasilar artery occlusions have not been well-studied. We compared clinical, procedural, and safety outcomes of MT for posterior circulation (PC) vs. anterior circulation (AC) occlusions among patients in the STRATIS registry. Methods: Data from STRATIS including patient demographics, procedural characteristics, and outcomes including symptomatic intracranial hemorrhage (sICH) at 24 h, serious adverse events (SAE), substantial reperfusion [modified thrombolysis in cerebral infarction (mTICI) 2b/3], 90-day functional independence [modified Rankin Scale (mRS) 0–2], and 90-day mortality were analyzed. Univariate logistic regression was used to calculate predictors of good clinical outcome. Results: Of 984 STRATIS patients, 43 (4.4%) patients with PC occlusions [mean age 63.0 ± 13.6, 25.6% (11/43) female] and 932 (94.7%) with AC occlusions [mean age 68.5 ± 14.8, 46.9% (437/932) female] were included for analysis. Median National Institutes of Health Stroke Scale (NIHSS) scores at baseline were 17.0 (13.0, 12.0) for the AC group and 12.0 (11.0, 24.0) for the PC group. Time from onset to procedure end was longer for the PC group [median (IQR): 322.0 min (255.0–421.0) vs. 271.0 min (207.0–360.0); p = 0.007]. PC and AC groups had similar rates of substantial reperfusion [89.2% (33/37) vs. 87.7% (684/780)], procedure-related SAE [0.0% (0/43) vs. 1.7% (16/932)], sICH [0.0% (0/38) vs. 1.5% (12/795)], 90-day functional independence [66.7% (26/39) vs. 55.9% (480/858)] and mortality [12.8% (5/39) vs. 15.8% (136/861)]. National Institutes of Health Stroke Scale score and patient sex were significant univariate predictors of good clinical outcome (p < 0.05). Conclusions: Despite longer reperfusion times, MT in PC stroke has similar rates of 90-day functional independence with no significant difference in procedure-related SAE, sICH, or mortality, supporting the use of MT in PC acute ischemic stroke (AIS). Clinical Trial Registration:https://www.clinicaltrials.gov, Identifier: NCT02239640.